Construction of pancreas-muscle-liver microphysiological system (MPS) for reproducing glucose metabolism - Lee, Dong Wook; Lee, Seung Hwan; Choi, Nakwon; Sung, Jong Hwan (WILEY, 2019)
Although in vitro models are widely accepted experimental platforms, their physiological relevance is often severely limited. The limitation of current in vitro models is strongly manifested in case of diseases where multiple organs are involved, such as diabetes and metabolic syndrome. Microphysiological systems (MPS), also known as organ-on-a-chip technology, enable a closer approximation of the human organs and tissues, by recreating the tissue microenvironment. Multiorgan MPS, also known as multiorgan-on-a-chip or body-on-a-chip, offer the possibility of reproducing interactions between organs by connecting different organ modules. Here, we designed a three-organ MPS consisting of pancreas, muscle, and liver, to recapitulate glucose metabolism and homeostasis by constructing a mathematical model of glucose metabolism, based on experimental measurement of glucose uptake by muscle cells and insulin secretion by pancreas cells. A mathematical model was used to modify the MPS to improve the physiological relevance, and by adding the liver model in the mathematical model, physiological realistic glucose and insulin profiles were obtained. Our study may provide a methodological framework for developing multiorgan MPS for recapitulating the complex interaction between multiple organs.
Keywords: ON-A-CHIP; INSULIN-CLEARANCE; DRUG DISCOVERY; DESIGN; MODELS; PHARMACOKINETICS; PRINCIPLES